"What citizens can see of the state": Police and the construction of democratic citizenship in Latin America. (November 2017) - González, Yanilda María
Police exercise the state's monopoly of legitimate use of force, a fundamental state function that shapes the construction of citizenship. What are the implications for citizenship when that monopoly is profoundly contested and unevenly distributed? This article explores this question in Latin America, where police confront historically high rates of crime and violence in the context of uneven state capacity and pervasive social inequality. Throughout Latin America, citizens lack the security necessary to engage in everyday political, economic, and social activities that are constitutive of citizenship, resulting in constrained citizenship . At the same time, citizens' everyday interactions and relationships to police reproduce existing social inequalities along lines of race, class, and geography, resulting in stratified citizenship . These policing practices and the concomitant constraints on and stratification of citizenship are mutually reinforcing, with troubling implications for state formation and democracy in the world's most violent and most unequal region.